Retail Drug Trade, Effects on Neighbourhoods, and Sellers’ Navigational Strategies: Accounts of Nigerian Dealers - Nelson, Ediomo-Ubong E. (Journal of drug issues, 2024)
Studies have examined the negative effects of drug markets on neighbourhoods. But few explore the views of drug sellers. Drawing on 31 in-depth interviews with Nigerian retail drug sellers, we explore why they sell drugs, the effects of drug markets on neighbourhoods, and how they navigate social and legal problems. The participants sold drugs as a means of livelihood in the context of poverty and economic decline. Drug market activities were seen as nuisance, and as fostering crime and violence in neighbourhoods. These views stirred opposition from residents and led to police raids on drug scenes. Drug sellers navigated policing and opposition by concealing drug trade, selling covertly and reducing nuisance among other strategies. We argue that retail drug trade is shaped by the imperatives of survival in the context of poverty. Providing alternative means of livelihood for drug sellers offers potential to curb drug selling and related problems.